Marriage Registration as a Legal-Political Arena in Islamic Family Law: Reinterpreting Maṣlaḥah Mursalah within Modern Legal Systems - Mukhamad Suharto; Nur Kholis; Ahmad Rezy Meidina; Muhammad Hasan Mahmud (Universitas Islam Tribakti Lirboyo Kediri, 2025)
Purpose – This article examines marriage registration in Islamic family law by positioning it as a legal-political arena, rather than merely an administrative requirement. Employing a qualitative socio-legal approach, this study investigates how the modern state constructs compulsory marriage registration as a mechanism for integrating Islamic norms, public interest, and legal pluralism. The analysis combines normative Islamic legal inquiry, historical examination of regulatory developments, and legal-political theories—particularly John Hart Ely’s representation-reinforcing theory, Savigny’s historical jurisprudence, and Mahfud MD’s contextual legal-political framework. Methods– This study employs a socio-legal method to examine marriage registration as a legal, social, and political construct within the framework of Islamic family law. Findings – The findings demonstrate that marriage registration signifies the transformation of Islamic family law from a community-based legal order into a state-centered legal system oriented toward rights protection, legal certainty, and social justice. From the perspective of maṣlaḥah mursalah and maqāṣid al-sharī‘ah, marriage registration functions as a legal mechanism to safeguard vulnerable groups, especially women and children, while simultaneously serving as a state instrument for shaping a legally recognized and administratively ordered family structure. Research implications – The main contribution of this article lies in proposing an analytical framework that conceptualizes marriage registration as a site of legal-political negotiation between the state, religion and society. By foregrounding power relations, legal policy, and normative integration, this study advances contemporary scholarship on Islamic family law and highlights the political dimensions of the regulation of family institutions in Muslim societies.